ANALISIS SEMIOTIK ATAS SAMPUL MAJALAH TEMPO JAKARTA "RIZAL RAMLI PETARUNG ATAU PERAUNG" - Yusra, Wildan; Hafiar, Hanny; Sjoraida, Diah Fatma (Informasi, 2017)
This study uses qualitative methods with semiotics analysis from Charles Sanders Peirce. The purposes of this study are to determine the symbol contained in MBM Tempo, the meaning contained within the symbol, and how these symbols constructing Rizal Ramli's Image as the howling. The result of this study showed MBM Tempo Jakarta cover "The Fighter or The Howling" 24-30 August 2015 Edition consist of three main symbols, Rizal Ramli's on his hips, pointing and opened mouth, a hand hold puppet stick, and text symbol. Rizal Ramli's caricature in the cover of MBM Tempo is an illustration of the text is written in the middle of Tempo's cover, so that both are interlocked. These symbols have different meanings. The meaning of each symbol constructing the image of Rizal Ramli as the howling in the cover of MBM Tempo. The conclusion of this study showed that the symbols MBM Tempo Jakarta cover "The Fighter or The Howling" 24-30 August 2015 Edition consist of three main symbols, Rizal Ramli's on his hips, pointing and opened mouth, a hand hold puppet stick, and text symbol included to typography. Abstrak Penelitian ini menggunakan metode kualitatif dengan analisis semiotika Charles Sanders Peirce. Tujuan penelitian ini adalah untuk mengetahui simbol yang terdapat dalam MBM Tempo, makna yang terkandung dalam simbol-simbol, dan simbol pada MBM Tempo dapat mengkonstruksi citra Rizal Ramli sebagai Peraung. Hasil penelitian menunjukkan sampul MBM Tempo Jakarta "Rizal Ramli Petarung atau Peraung" Edisi 24-30 Agustus 2015 terdiri dari tiga simbol utama, simbol gesture Rizal Ramli sedang berkacak pinggang, menunjuk dan mulut terbuka, simbol tangan wayang yang memegang tuding, dan simbol teks. Karikatur Rizal Ramli yang terdapat dalam sampul MBM Tempo merupakan ilustrasi dari teks yang tertulis ditengah sampul Tempo, sehingga keduanya saling berkaitan. Simbol-simbol tersebut memiliki makna yang berbeda-beda. Makna yang terkandung dari setiap simbol mengkonstruksikan citra Rizal Ramli sebagai Peraung dalam sampul MBM Tempo. Kesimpulan penelitian ini adalah terdapat tiga simbol utama dalam sampul MBM Tempo Jakarta "Rizal Ramli Petarung atau Peraung" Edisi 24-30 Agustus 2015, yaitu simbol gesture Rizal Ramli sedang berkacak pinggang, menunjuk, dan mulut terbuka, simbol tangan wayang yang memegang tuding, dan simbol teks yang termasuk tipografi.